MENERAPKAN PEMBELAJARAN SEJARAH BERBASIS DIGITAL DI SMAN 2 ROKAN IV KOTO - Ahya Sofia Balqis; Aswadtun Hasanah; Ella Putri Astuti; Elsa Mayangsari; Lisa Oktafindari; Nada Mutia Zahara; Putri Mala Sari Lubis; Riszky Wahyu Winoto; Sherly Harvido Reza; Zukri, Zukri (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Information technology that has developed so rapidly in the era of globalization has had an impact on various field, one of which is the field of education in implementing digital-based learning media. This application is carried out to provide students with understanding and interest in understanding history learning. In this activity understanding and skills are required so that Universitas Riau Community Service Student teach at SMAN 2 Rokan IV Koto with the aim of introducing digital-based history learning using the method of providing educational videos about Indonesia History during the period of Imperialism and colonialism as a starting point in understanding history. The conclusion of this activity shows that students can understand the impact on colonized nations and the implications for the development of the modern world. In addition, teaching about colonialism and imperialism can also help student understand contemporary social and political issues related to colonial heritage